Odpowiedzi

2010-01-05T14:52:50+01:00
2x-0,5y=3
y-4x=-6

0,5y=3-2x//(-0,5)
y-4x=-6

y=1,5-x
y-4x=-6

y=1,5-x
1,5-x-4x=-6

y=1,5-x
-5x=-7,5

y=1,5-x
x=1,5

y=-6+4*1,5
x=1,5

y=-6-6
x=1,5

y=-12
x=1,5


przykład 2
6x+y=3
3x+0,5y=5

y=3-6x
3x+0,5(3-6x)=5

y=3-6x
3x-1,5-3x=5

y=3-6x
0=6,5

zadanie nie ma rozwiązania
2010-01-05T14:55:15+01:00

2x-1/2y=3 // × 2
y-4x=-6

4x -y=6
y-4=-6 //+4

4x -y=6
y=-2

4x-(-2)=6
y=-2

4x+2=6 //-2
y=-2

4x=4 // ÷ 4
y=-2

x=1
y=-2

drugi przykład

6x+y=3
3x+1/2y=5 //×2

6x+y=3 / × (-1)
6x+y=10

-6x-y=-3
6x+y=10

-6x+6x+-y+y=7
0=7
układ sprzeczny

mam nadzieje ze dobrze :)